Antioxidant Interactions between Citrus Fruit Carotenoids and Ascorbic Acid in New Models of Animal Cell Membranes - Marcelo P. Barros; Jaime Zacarías-Garcia; Florencia Rey; Lorenzo Zacarías; María J. Rodrigo (MDPI AG, 2023)
The regular consumption of citrus fruits by humans has been associated with lower incidence of chronic-degenerative diseases, especially those mediated by free radicals. Most of the health-promoting properties of citrus fruits derive from their antioxidant content of carotenoids and ascorbic acid (ASC). In the current work we have investigated the scavenging (against hydroxyl radical) and quenching capacities (against singlet oxygen) of four different carotenoid extracts of citrus fruits in the presence or absence of ASC (μM range) in organic solvent, aqueous solution, micelles and in an innovative biomimicking liposomal system of animal cell membrane (AML). The fruits of four varieties of citrus were selected for their distinctive carotenoid composition (liquid chromatography characterization): 'Nadorcott' mandarin and the sweet oranges 'Valencia late', 'Ruby Valencia' and 'Pinalate' mutant. The quenching activity of citrus carotenoids strongly depended on the biological assemblage: freely diffusible in organic solvent, 'Ruby Valencia' carotenoids (containing lycopene) showed the highest quenching activity, whereas 'Nadorcott' mandarin extracts, rich in β-cryptoxanthin, prevailed in micellar systems. Interestingly, the addition of 10 μM ASC significantly increased the quenching activity of all citrus extracts in micelles: 'Valencia' orange (+53%), 'Pinalate' (+87%), 'Ruby' (4-fold higher) and 'Nadorcott' mandarins (+20%). Accurate C11-BODIPY581/591 fluorescence assays showed solid scavenging activities of all citrus extracts against AML oxidation: 'Valencia' (−61%), 'Pinalate' (−58%) and 'Ruby' oranges (−29%), and 'Nadorcott' mandarins (−70%). Indeed, all four citrus extracts tested here have balanced antioxidant properties; extracts from the 'Nadorcott' mandarin slightly prevailed overall, due, at least in part, to its high content of β-cryptoxanthin. This study depicts some of the antioxidant interactions between citrus fruit carotenoids and ascorbic acid in models of animal cell membranes and reinforces the contribution of them in promoting health benefits for humans.